Scenes From Tick Physiology: Proteins of Sialome Talk About Their Biological Processes - Fernández-Ruiz, Natalia; Estrada-Peña, Agustín (Frontiers in Cellular and Infection Microbiology, 2022)
Ticks are blood-sucking parasites that operate different feeding strategies based on the family they belong to. The major families are the slow-feeding Ixodidae and fast-feeding Argasidae. Recent advances in molecular sequencing techniques have contributed to acquire knowledge about the proteome of the tick’s salivary glands. However, the biological processes underlying the expression of sialome remain poorly understood. In this study, we employed biological processes as a tool to determine the physiology of the tick’s salivary glands, using published data on the sialome of Rhipicephalus sanguineus s.l. (Ixodidae) and Ornithodoros rostratus (Argasidae). The proteins described in the published data were subjected to a quality control. Next, we obtained the biological processes in which each protein was involved. We developed a directed network construct wherein nodes represented proteins (the source) and biological processes (the target) for low-level (“children”) and top-level (“parents”) processes, separately. Network constructs were also developed for several groups of feeding R. sanguineus and different organs of O. rostratus. The network connected the proteins and processes with a strength directly proportional to the transcript per million reads of each protein. We used PageRank to measure the importance of each process. This approach describes the biological processes of feeding R. sanguineus with interesting observations. The sialome of unfed R. sanguineus expressed approximately 30% fewer biological processes than that of feeding ticks. Another decrease (25%) was noted in ticks at the middle of the feeding period and before detachment. However, top-level processes were deeply affected at the onset of feeding. Significant differences were observed when comparing an argasid with an ixodid. For example, 91% of proteins were not shared between them; however, an absence of only 10% of biological processes was noted. Different proteins probably displayed the same biological function in both ticks. The gut and salivary glands of O. rostratus expressed almost the same processes, with a higher PageRank detected for the gut. Considering the limitations in annotating the tick’s proteins, we propose to employ the networks of sialome proteins and their biological processes as a tool to define the landscape of the physiology of the feeding process.